Assembly of Carbon Nanotubes between Electrodes by Utilizing Optically Induced Dielectrophoresis and Dielectrophoresis. (19th September 2011) - Wu, Pei-Fang; Lee, Gwo-Bin
Abstract : This study reports a new approach for assembling carbon nanotubes (CNTs) between electrodes combination of optically induced dielectrophoresis force and dielectrophoresis force. Metal electrodes and amorphous silicon layer were first patterned and then used to assemble CNTs. By utilizing moving light patterns, the CNTs could be collected to the central area between two metal electrodes. The CNTs with different concentrations can be collected and aligned to form CNTs lines with different widths. The immobilization of preassembled CNTs was also demonstrated by exposing them to an ultraviolet light source such that they can be fixed at the prealigned location. Then photoresist asher was used to get rid of the cured polymer. The development of the new platform can be promising to massively assemble CNTs.